Application of make a match model to improve geography learning outcomes - Deasy Arisanty; Riyah Riyah (OmniaScience, 2019)
This research was conducted to analyze the application of make a match learning model to improve the learning outcome of geography in class X of SMA PGRI 4 Banjarmasin with the material of geography principles. This research employed a quasi-experimental design method, quantitative approach and non-equivalent of pre-test and post-test control group design. The research included two groups namely the control and experimental groups. The number of the population was 67 students. All students in class X were used as the samples, where class X 1 was as the experimental class and X2 was as the control class. Students in class X 1 and X-2 were 35 students and 32 students.  The result of t-test showed that the value of post-test for experimental class using make a match learning model was 54.87. The post-test result from the control class using the conventional model was 48.05. The post-test using the make a match had the higher learning outcome than the conventional model. The make a match learning model had increased the student learning outcome of geography.